Generalized method of computer-aided design of technological processes for MEMS accelerometers manufacturing - I. Sh. Nevliudov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A generalized method for the automated design of technological processes for the production of MEMS accelerometers is developed. This method is based on two methods: the method of selecting a standard technological processes and the method of searching for analogues of individual subsystems and elements of MEMS accelerometers, which will increase the efficiency of design work by reducing the cost and time of manufacture. Within the framework of the method, decision-making model to select the type of MEMS accelerometer for its functionally constructive parameters, model for searching analogues of individual subsystems and MEMS accelerometer elements, as well as a model for selecting equipment that, based on 4 indicators: productivity, energy efficiency, equipment price, service have been developed.